2019
DOI: 10.1182/blood-2019-124512
|View full text |Cite
|
Sign up to set email alerts
|

Combined Retro- and Prospective Analysis of Adherence to Guidelines and Patient-Tailored Therapeutic Recommendations in Patients with Myelodysplastic Syndromes (MDS) at a Tertiary Care Centre

Abstract: Introduction The effect of adherence to treatment guidelines has not yet been evaluated in myelodysplastic syndromes (MDS). Based on the large Düsseldorf MDS Registry, we explored adherence to European LeukemiaNet (ELN) guidelines as well as MDS expert recommendations in clinical routine. Methods In a preliminary retrospective analysis of 1658 patients documented in the Düsseldorf MDS registry, we reviewed if treatment was in accordance with the published ELN guidel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…A recent prospective and retrospective analysis of MDS patients treated in a tertiary care center in Germany showed that adherence to allo-HSCT G/Rs resulted in improved survival, whereas adherence to other treatments did not. 49 These data underscore the impact of allo-HSCT G/Rs on survival, whereas the benefit of less-intensive treatments on additional patient-centered outcomes remains difficult to be captured in post hoc studies.…”
Section: Discussionmentioning
confidence: 99%
“…A recent prospective and retrospective analysis of MDS patients treated in a tertiary care center in Germany showed that adherence to allo-HSCT G/Rs resulted in improved survival, whereas adherence to other treatments did not. 49 These data underscore the impact of allo-HSCT G/Rs on survival, whereas the benefit of less-intensive treatments on additional patient-centered outcomes remains difficult to be captured in post hoc studies.…”
Section: Discussionmentioning
confidence: 99%